Simulated muscle activity in locomotion: implications of co-occurrence between effort minimisation and gait modularity for robot-assisted rehabilitation therapy. Issue 12 (6th October 2021) - Maddalena, Marco; Saadat, Mozafar
Abstract: Evolution of gait rehabilitation robotic devices for stroke survivors has aimed at providing transparency to user's efforts and implementing 'assist-as-needed' paradigm. Alteration of muscle activity and synergies recruitment has been noticed in trials involving healthy subjects but no analytic tool has been proposed to understand root causes. In this paper, a simplified neuro-mechanical model is introduced for simulating lower limbs' muscle activity during unrestrained and device-constrained gait, taking into consideration exoskeleton-plus-treadmill and end-effector categories. Muscle control is based on the key hypothesis that optimality criterion pursues co-occurrence between effort minimisation and modularity during regular gait. Results highlight that modelised motion constraints on lower body raise additional redundancies which alter muscle activity and increase intervention external to unrestrained gait synergies. Accordingly, the developed simulations help to identify the inherent limitations of current technology: further degree of freedom addition to exoskeleton-plus-treadmill device could be useful but impractical, while end-effector devices would benefit significantly from an improved interaction management.